Transportation Schedule-Respected Production Planning Using Genetic Algorithm Based Approach - Doležel Petr; Heckenbergerová Jana; Mariška Martin; Škrabánek Pavel (Springer, 2015)
In this contribution, there is introduced a genetic algorithm for the production planning issue solving while shipping of the products to the purchasers is respected. The aim of the paper is to provide a search technique that minimizes the objective function composed of the joint costs of production (manufacturing line rearrangement minimization), transportation (delivery route minimization) and holding (shipping date optimization) while all the purchasers' orders are delivered within the de ned horizon. This class of issues is considered to be a NP-hard combinatorial problem and it is not possible to solve it analytically for large amounts of inputs. Thus, the stochastic approach is proposed in this paper. This approach, which is based on the genetic algorithm, respects all the components of the objective function and provides acceptable solution in reasonable time as discussed at the end of the paper.
Algoritmus pro plánování výroby s ohledem na optimalizaci dopravy pomocí genetického algoritmu
Keywords: evolutionary algorithms; production planning; optimization; NP-hard problems